Urban Regeneration and Local Expectations: The Case of the Central Garage District, Bursa-Turkey - Polat, Sibel; DOSTOĞLU, NESLİHAN (My University, 2010)
In recent years, different arguments have been made about urban regeneration in Turkey, similar to many other countries in the world. Instead of a comprehensive approach suggesting new partnerships between local authorities and citizens, urban regeneration in Turkey has been generally used as a populist instrument of local authorities mostly to produce physical solutions for political gains in the short run. In this study, the case of Central Garage District in Bursa will be discussed as an example of urban regeneration implementation which started with the aim of rehabilitating a neglected urban area, but which resulted in an urban regeneration process deprived of social/cultural and organizational aspects.
Keywords: Urban regeneration; Local participation; Social inclusion; Central Garage; City Square; Bursa